2000
DOI: 10.1117/1.429996
|View full text |Cite
|
Sign up to set email alerts
|

Modeling photon transport in transabdominal fetal oximetry

Abstract: The possibility of optical oximetry of the blood in the fetal brain measured across the maternal abdomen just prior to birth is under investigation. Such measurements could detect fetal distress prior to birth and aid in the clinical decision regarding Cesarean section. This paper uses a perturbation method to model photon transport through an 8-cm-diam fetal brain located at a constant 2.5 cm below a curved maternal abdominal surface with an air/tissue boundary. In the simulation, a near-infrared light source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Subsequently, Zourabian et al developed a transabdominal NIR CW oximeter with the capability to detect fetal arterial pulses in utero [301]. In addition, theoretical and experimental tissue phantom investigations have been performed to understand NIR photon diffusion through the fetal brain in utero [138,270]. Collectively, these studies suggest transabdominal NIR photon diffusion measurements through the fetal brain in utero are possible.…”
Section: Fetal Brain Oxygenation Monitoringmentioning
confidence: 99%
“…Subsequently, Zourabian et al developed a transabdominal NIR CW oximeter with the capability to detect fetal arterial pulses in utero [301]. In addition, theoretical and experimental tissue phantom investigations have been performed to understand NIR photon diffusion through the fetal brain in utero [138,270]. Collectively, these studies suggest transabdominal NIR photon diffusion measurements through the fetal brain in utero are possible.…”
Section: Fetal Brain Oxygenation Monitoringmentioning
confidence: 99%
“…The use of NIRS in neonatology and obstetrics dates back to the mid 1980s and has been used for interrogation of both fetal and maternal tissues in all stages of pregnancy (Brazy et al 1985;O'Brien et al 1992;Baños et al 2007). Antepartum NIRS, the application currently under investigation, began with photon migration studies (Jacques et al 2000;Ramanujam et al 2000;Vishnoi et al 2000), and has since matured into a means of monitoring fetal and placental tissues in utero via spatially resolved, transabdominal NIRS.…”
Section: Nirs In Obstetrics and Neonatologymentioning
confidence: 99%
“…Previous studies have demonstrated, through simulations, [18][19][20][21][22] phantom models, 23 and in vivo experiments, 22,24 the feasibility of detecting NIR photons that have penetrated an underlying fetal layer, centimeters deep. There has been a discussion among investigators as to which photon diffusion model most accurately describes photon propagation through a two-layer model, 11,12,14,16,22 such as that described here.…”
Section: Introductionmentioning
confidence: 99%